News article named entity recognition and analytics - Goh, Nicholas (Nanyang Technological University, 2022)
Text analytics have been essential in today’s data driven world. Search engines such as Elasticsearch are widely used to retrieve documents based on user queries that would otherwise be impossible for a human to manually sift through and retrieve. NER models classify important phrases in a paragraph of text. Feature vectors can be extracted from NER models to compare similarity between different texts. However, there has been little work where these 3 tools have been used together.